Improved hybrid particle swarm optimisation for image segmentation. Issue 1 (2nd January 2021) - Liu, Shuo; Zhou, Kang; Qi, Huaqing; Liu, Jiangrong
Abstract : A method for image segmentation based on improved hybrid particle swarm optimisation (PSO) is proposed. In view of the shortcoming that the traditional PSO algorithm is easy to fall into local optimal solution, we update the particle velocity based on the combination of global optimisation, region equilibrium and compression factor. By this way, the searchability of the particle and optimisation performance of the improved PSO is improved. Experiments results on three classic test functions show that the algorithm can greatly improve the searchability. Experiments also show that it performs well on image segmentation. GRAPHICAL ABSTRACT: